Assessment of the design–construction interface problems in the UAE. (2nd September 2016) - AL Mousli, Mohamad Hazem; El-Sayegh, Sameh Monir
ABSTRACT: Design–construction interface problems impede the successful delivery of construction projects within the specified time, cost and quality. The objective of this paper is to assess the design–construction interface problems in the United Arab Emirates (UAE) construction industry. Twenty-two problems were identified through literature review. A questionnaire survey was then developed and distributed to construction professionals. Thirty-nine responses were collected from consultants, contractors and construction professionals in government authorities. The weighted average of the responses was calculated. The results reveal that the most significant interface problems in the UAE include lack of coordination inside the design firm, lack of specialist construction manager, poorly written contract, lack of project management as individual professional service and time limitation in the design phase. Moreover, the paper analysed the responses according to company role. Most of these problems are caused by the lack of coordination and communication among the main contracting parties. Recommendations are made to enhance the coordination and management of construction projects that lead to reduction in the design–construction interface problems.